The analysis of innovation input - output relationships in EU member states; Analiza powiazanńakładoẃ i efektoẃ działalnosći innowacyjnej w krajach UE - Arkadiusz Kijek; Tomasz Kijek (Comparative Economic Research. Central and Eastern Europe, 2010)
This article presents some findings of an analysis of innovation input - output relationship in EU member states. The first section of the paper considers the role of innovation in economic growth with particular attention to the new endogenous growth models. In the second part, the dichotomous approach to innovation and its measures is presented. The last section contains the methodology and outcome of research. The results of the study show that R&D expenditures, ICT and human capital are the key innovation inputs that affect such innovation outputs as innovation and patent propensity and new-to-market sales. – – Prezentowany artykuł przedstawia wyniki analizy powiazanńakładoẃ i efektoẃ działalnosći innowacyjnej w krajach UE. W pierwszej czesći opracowania przedstawiono role innowacji w kreowaniu wzrostu gospodarczego ze szczegoĺnym uwzglednieniem nowych modeli wzrostu endogenicznego. W drugiej czesći pracy scharakteryzowano pojecie i mierniki innowacji w ujeciu dwuwymiarowym. Ostatnia czesćártykułu prezentuje metodyke i wyniki badania. Zgodnie z nimi wydatki na BiR, technologie informacyjno komunikacyjne oraz kapitał ludzki, traktowane jako wkład w proces innowacyjny, maja istotny wpływ na wyniki działalnosći innowacyjnej, w szczegoĺnosći na skłonnosćd́o innowacji i patentowania oraz przychody ze sprzedazẏ nowych produktoẃ.
Keywords: 330